Acute pancreatitis, a significant mortality predictor in acute organophosphate poisoning: an observational study in a tertiary care centre in north India - Tomar, Aditya; Singh, Reena; Kumar, Vinay; Kaur, Samarjeet (International Journal of Advances in Medicine, 2023)
Background: Organophosphate compounds are one of the most common agents used as poison and acts by accumulation of acetylcholine hormone at neuronal synapses resulting in the symptoms like excessive salivation, vomiting, urination, and increased serum amylase and lipase levels. APACHE 2 score along with ultrasound modality can be used to assess the acute pancreatitis. The primary aim of the study is to find correlation of serum amylase and lipase levels with duration of ICU stay and with radio-logical variables like bulky pancreas. Methods: This observational study conducted at GSVM medical college, Kanpur from December 2020 to October 2022 included 58 out of total 94 admitted patients with acute organophosphate intoxicationn on the basis of inclusion and exclusion criteria. Patients were divided in 3 groups as mild, moderate and severe using q SOFA score at the time of admission. Results: Acute organophosphate poisoning was more prevalent among 20-40 years of age group. Mean serum amylase level values in q SOFA category 0, 1, 2, 3 were 65.2, 82.0, 118.4, 329.9 IU/l respectively and that of mean serum lipase levels on day 1 of admission values were 42.0, 44.3, 38.6 and 115.5 IU/l respectively. Serum amylase levels were positively correlated with duration of ICU stay and were better predictor for acute pancreatitis. Conclusions: In this study we concluded that serum amylase is a better predictor of duration of ICU stay and acute pancreatitis in patients admitted with acute organophosphate poisoning.